1980
DOI: 10.1073/pnas.77.1.634
|View full text |Cite
|
Sign up to set email alerts
|

Substance P enhances cholinergic receptor desensitization in a clonal nerve cell line.

Abstract: Substance P inhibits carbamylcholine-induced 22Na+ uptake in the clonal cell line PC12. This inhibition is noncompetitive with agonist but comretitive with Na+. Octahydrohistrionicotoxin (H8-HTX) also e iibits this same pattern of inhibition. Moreover, both substance P and HrHTX are very effective in enhancing agonist-induced receptor desensitization. Local anesthetics, such as QX222, also cause inhibition that is competitive with Na+, but they have only marginal effects on desensitization. Because substance P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
1

Year Published

1982
1982
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(57 citation statements)
references
References 25 publications
6
50
1
Order By: Relevance
“…Reports on the effect of SP on desensitization of the nicotinic response are controversial, some studies reporting SP protects against desensitization (Boksa & Livett, 1984b;Khalil et al, 1988a) while others find it enhances the rate of nicotinic desensitization (Stallcup & Patrick, 1980;Clapham & Neher, 1984;Simasko et al, 1985;Higgins & Berg, 1988 (Boyd, 1987). Boyd & Leeman (1987) showed that SP increased agonist-induced desensitization of nicotinic receptors in the fast phase but inhibited agonist-mediated desensitization in the later slow phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports on the effect of SP on desensitization of the nicotinic response are controversial, some studies reporting SP protects against desensitization (Boksa & Livett, 1984b;Khalil et al, 1988a) while others find it enhances the rate of nicotinic desensitization (Stallcup & Patrick, 1980;Clapham & Neher, 1984;Simasko et al, 1985;Higgins & Berg, 1988 (Boyd, 1987). Boyd & Leeman (1987) showed that SP increased agonist-induced desensitization of nicotinic receptors in the fast phase but inhibited agonist-mediated desensitization in the later slow phase.…”
Section: Discussionmentioning
confidence: 99%
“…This inhibitory action of SP was markedly enhanced by pre-exposure to SP for 10min before nicotine (Figure 4). Inhibitory effects of SP on the nicotinic responses have been described for a number of different preparations including cat spinal Renshaw cells (Belcher & Ryall, 1977;Krnjevic & Lekic, 1977), bovine isolated chromaffin cells (Livett et al, 1979;Role et al, 1981;Boksa & Livett, 1984b), frog sympathetic ganglia and skeletal muscle endplates (Akasu et al, 1983), (Stallcup & Patrick, 1980;Simasko et al, 1985;Boyd & Leeman, 1987), BC3H1 cells (Simasko et al, 1985) and rat adrenal gland slices (Nieber & Oehme, 1987). This action which is Ca2"-dependent and specific to nicotinic receptor function (Boksa & Livett, 1984b;Role et al, 1981) has an IC50 for SP of about 10-6M (Boksa & Livett, 1984b;Simasko et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to muscle nAChRs, some early studies showed that the time course of desensitization onset for ganglionic nicotinic receptors could be enhanced by phorbol ester activation of protein kinase C (PKC) (Dowining and Role, 1987), in a similar manner to that produced by the peptide, substance P (Stallcup and Patrick, 1980;Role, 1984). More recent studies have focused on elucidating the biochemical pathways necessary for these types of effects and their structural basis.…”
Section: Regulation Of Desensitizationmentioning
confidence: 99%
“…The PC12 cell line (Greene and Tischler, 1976) shares many properties with sympathetic neurons and has thus provided an extremely useful model system for studying several types of neuronal mechanisms, including the function of neuronal acetylcholine receptors (Patrick and Stallcup, 1977a, b;Stallcup and Patrick, 1980;Dichter et al, 1977), Na+ channels (Stallcup, 1979;Dichter et al, 1977), Ca2+ channels (Stallcup, 1979;Ritchie, 1979), K' channels (Arner and Stallcup, 1981), the synthesis and secretion of acetylcholine and catecholamines (Ritchie, 1979;Schubert et al, 1977;Greene and Rein, 1977), and the response to nerve growth factor (McGuire et al, 1978;Schubert et al, 1978). In light of the many similarities between PC12 cells and neurons, it seems likely that antisera raised against PC12 cells might define cell surface antigens specific to neurons.…”
mentioning
confidence: 99%